PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 022 SINTONG KECAMATAN TANAH PUTIH - Dana, Asia; Zulkifli, Zulkifli; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of research study is that the learning outcomes of students categiruzed IPS is still low because students are still difficulties in accepting the lesson, the student are less active in learning, the teacher is less engaging students in learning and teachers only use the lecture method,and student are less involved directly to determine their own knowledge holds. Of these problems need to be a Class Action Research (PTK) by applying the learning mode cooperative mode throwing snowball . this research aims to improve learning outcomes IPS grade IV SDN 022 districts Sintong white ground with a number of students as many as 20 students. This research was conducted in two cycle by with one daily testa. Data collection instruments in reseach is observation sheet and test results of learning. Result of the data analysis of the teacher in cycle one the first meeting and 69.4% increase to 80,6% on the second cycle firs meeting 88,9% and second meeting increase to 97,2%.While the results of the data analysis activity of students in the first cycle the first meeting and the second meeting 63,9% and the second meeting increase to 77,8%. In the second meeting of the 83,3% and the second cycle the firs meeting increase to 94,4%. From the result of this study showed that student learning has incrased an average score of student learning outcomes is 63,25 basis increased to 70,5 in the first cycle increased again in the second cycle in 80,00. For mastery learning on the base score is 8 people (40%) increased in the first cycle to 12 people (60%) increased again in the second cycle to 18 people (90%). Thus we can conclude that if applied learning cooperative model throwing snowball mode can improve learning outcomes IPS grade IV SDN 022 dictrict Sintong white ground.Keywords: Model Cooperatif Learning Type Snowball Throwing Student Achiement of science Studies